Estimation of prevalence and risk factors for clostridium difficile infection: a neglected pathogen in a tertiary care setting in India - Lall, Sujata; Nataraj, Gita; Mehta, Preeti (International Journal of Medical Research and Review, 2017)
Introduction: Clostridium difficile is a Gram positive spore bearing anaerobic bacillus increasingly associated with both community and hospital acquired colitis and diarrhoea. Among all the risk factors, inclusive of the host and the environmental factors, antibiotics are the most important ones, as validated by various studies. Patients receiving antibiotics and other drugs such as immunosuppressives, chemotherapeutics and proton pump inhibitors may also be important risk factors. The present study was planned to find out the prevalence and risk factors for Clostridium difficile associated diarrhoea (CDAD). Material and Methods: After taking approval from ethics committee ,150 patients with antibiotic associated diarrhoea were taken as study group and 50 patients with exposure to antibiotics but who did not develop diarrhoea were taken as controls. Stool specimens were processed for both culture on Cycloserine Cefoxitin Fructose Agar (CCFA) and toxin detection by IVD Tox A+B ELISA. Risk factor analysis was done by calculating odds ratio and significance of p value among various parameters related to drugs and other factors. Result: Prevalence of CDAD in the present study was 8.67%.Third generation cephalosporins, clindamycin, aminoglycosides, quinolones and trimethoprim sulfamethoxazole were significant risk factors for both antibiotic associated diarrhoea (AAD) and Clostridium difficile associated diarrhoea (CDAD).Use of proton pump inhibitors, immunosuppressants and prolonged stay in the hospital were other significant risk factors associated with CDAD. Conclusion: Although CDAD occurs at a lower frequency in this setting, rational antibiotic policy and infection control measures should be followed to prevent its occurrence and nosocomial spread.